Export Product Range and Economic Performance – An Emphasis on Small Advanced EU Countries - Ville Kaitila (The Research Institute of the Finnish Economy (ETLA), 2017)
We analyse the number of different HS8 products in the EU countries' ex-ports in 1995–2015. We review what share, or coverage, of the total possible number of these products the countries exported each year. We analyse whether the development in this coverage rate as opposed to concentration of exports as measured by the Herfindahl–Hirschman index is associated with GDP per capita growth. We find that changes in the coverage rate relate positively, but that the development of the HH index has no statistically significant relation to economic growth.
Keywords: F14; F43; O47; 330; Exports; Export products; GDP growth; EU